A study to determine association of the interval between seizure and delivery with the APGAR scores and perinatal asphyxia of the neonates of eclamptic mothers of a rural tertiary care hospital in Eastern India - Bandyopadhyay, Santanu; Burman, Medhatithi; Datta, Asok Kumar (International Journal of Contemporary Pediatrics, 2020)
Background: Eclamptic seizure not only affects maternal health but may predispose low APGAR scores and development of perinatal asphyxia and thereby influence perinatal mortality too. This study was carried out to evaluate the correlation of the interval between the onset of seizure and delivery with the APGAR scores (at 1 minute and 5 minutes) and perinatal asphyxia of the neonates of the eclamptic mothers. Methods: A prospective, cross-sectional, observational, epidemiological study was conducted from April, 2012 to March, 2013 at a tertiary-care Government teaching hospital catering rural population of Eastern India. The participants comprised of 100 consecutive admitted eclamptic mothers and neonates born to them. Results: Majority of mothers were unbooked, primigravidae (86%), aged below 20 years (66 %). Significant inverse correlation was observed between seizure to delivery interval and Apgar scores (1 min and 5 minutes), while seizure to delivery interval >12 hours was found to be a significant risk factor for perinatal asphyxia (OR =16.824, 95% CI = 5.107-55.424, p <0.001). Conclusions: Measures to minimise the interval between the onset of seizures and delivery will decrease the incidence of perinatal asphyxia and perinatal mortality of neonates of eclamptic mothers in rural areas.